Sistem Informasi Geografis untuk Mendukung Peta Risiko Banjir di Kecamatan Parengan dengan Metode Scoring - Sandy, Rio Ary; Rodhi, Nova Nevila; Saputra, Ichwan Hadi (LPPM STIKOM Tunas Bangsa, 2024)
Tuban Regency, was identified as a high risk disaster area which was ranked 145th out of 496 districts/cities in Indonesia that are vulnerable to disasters by the National Disaster Management Agency (BNPB). In the Tuban area, the last flood occurred on November 30 2022, especially in Parengan District. Flooding in Parengan District was caused by the river overflowing due to excessive water volume, causing inundation in low areas. The aim of this research is to anticipate the danger of flooding, early mitigation efforts are very important, which requires the development of mapping to determine vulnerable areas in Parengan District. The expected result is the production of an analysis map that describes the level of flood vulnerability in Parengan District. The method used in this research is GIS-based modeling and descriptive analysis of the processed data. Modeling via GIS uses the QGIS 3.24.1 application by applying the Scoring process or giving scores to each class for each parameter and overlay. The results of the Overlay analysis illustrate that Parengan District can be classified into three categories, namely not vulnerable, vulnerable and very vulnerable.